Training and Maintaining: Developing a Successful and Dynamic Continuous Renal Replacement Therapy Program. (2017) - Przybyl, Heather; Evans, Jill; Haley, Laurie; Bisek, Jodi; Beck, Emily
ABSTRACT : N/A: Continuous renal replacement therapy (CRRT) is commonly used to support critically ill patients with acute kidney injury or chronic renal disease whose condition is too unstable for them to tolerate intermittent hemodialysis. Current publications related to CRRT programs in the United States and Canada note key themes related to the development and maintenance of CRRT training programs. A successful CRRT training program should consider and incorporate adult learning principles whenever possible. A variety of teaching methods to deliver information to nurses, including online learning modules, didactic lecture, return demonstration, and high‐fidelity patient simulation are key to training programs for this high‐risk complex therapy. This article outlines the approach to training nurses to care for patients receiving CRRT at a health care system in Arizona.